Handbook of research on disaster management and contingency planning in modern libraries - Decker, Emy Nelson 1978-; Townes, Jennifer A. 1981- (Hershey, PA Information Science Reference, 2016)
"This book brings together the latest scholarly research, theories, and case studies to investigate the scale and types of disasters that can impact a library"--Provided by publisher.
Includes bibliographical references (pages 625-660) and index.
Keywords: Library buildings -- Safety measures; Library buildings -- United States -- Safety measures; Libraries -- Security measures -- United States; Library materials -- Conservation and restoration -- Planning; Emergency management -- United States